Utilising online eye-tracking to discern the impacts of cultural backgrounds on fake and real news decision-making - Brockinton, Amanda; Hirst, Sam; Wang, Ruijie; McAlaney, John; Thompson, Shelley (Frontiers in Psychology, 2022)
Online eye-tracking has been used in this study to assess impacts of different cultural backgrounds on information discernment. An online platform called RealEye allowed participants to engage in the eye-tracking study from their personal computer webcams, allowing for higher ecological validity and a closer replication of social media interaction. The study consisted of two parts with a total of five visuals of social media posts mimicking news posts in Twitter, Instagram, and Facebook. Participants were asked to view examples of real and fake news taken from a news fact-checking website, Snopes, and their eye movements were recorded during the process. Participants were recruited through Prolific and SONA, total sample size for study 1.1 = 29 participants, and total for study 1.2 = 25 participants, after removing poor eye-tracking data. A total of five visual images comprising of true and false news were shown to the participant, study 1.1 had three examples and study 1.2 had two examples. There were two main cultural backgrounds in focus; participants born in China or in the United Kingdom. Results suggested that participants follow a similar visual pattern of attention to Areas of Interest (AOIs) on the posts, which leads us to believe that due to the global standardisation of popular social media platforms, a bias might have occurred during information discernment. This suggests that users, regardless of country background, may have similar eye-tracking result while viewing a social media post because social media platform formats are standardised globally.